Gender Ratio Imbalance Effects on HIV Risk Behaviors in African American Women - Newsome, Valerie (Health Promot Pract, 2012)
Although literature suggests that African American women are no more likely to engage in risky sex than their White counterparts, they are more likely to have sex partners with higher HIV risk. Thus, it is not solely an individual’s behavior that determines their risk, but also the behavior of their partner and their position within a sexual network. For this reason, it is important to consider the dynamics of heterosexual relationships in the African American community. An important area of concern regarding African American heterosexual relationships is that of partner availability. A shortage of available African American men for potential partnerships exists and is reportedly due to poorer health and higher mortality rates. Some have argued that gender-ratio imbalance may be responsible for increased HIV vulnerability for African American women. This article reviews the literature on gender ratio imbalance and HIV risk in the African American community, and presents implications and suggestions for future research and intervention.